Home Automation System (HAS) Using Android Bluetooth Control Device (ABCD) Modul As a Controller of Electrical Devices - Gitakarma, Made Santo (JST (Jurnal Sains dan Teknologi), 2018)
Home Automation System (HAS) is a widely used reference term for system of controlling, monitoring, and home automation functions. HAS generally require a smartphone application or web portal as its interface. The electrical devices can be controlled by a switch, timer, sensor or remote control. In this paper we describe the module for controlling devices with applications from smartphones via a Bluetooth connection called Android Bluetooth Control Device (ABCD). This module is packaged portable and can be used in classroom learning or demonstrated to people who want to know the working principle of this module. The approach used is controlling 8 devices consisting of 4 lights and 4 additional devices. The module is controlled with smartphone application via bluetooth using bluetooth HC-05 which works on 2.4 GHz frequency with maximum range of 10 m. ABCD module can be used to facilitate the user in controlling various electrical devices at home.